Mapping mollic epipedon thickness via ground-penetrating radar based on the combined method of Variational Mode Decomposition and Average Envelope Amplitude - Haipeng Lu; Xiangming Zhu; Wenjuan Zheng; Bin Zhang; Tianhao Wang; Yu Zhang; Meiling Fu; Enhua Ran (Soil and Tillage Research, 2026)

Genome-wide characterization of terpene synthase genes in Ginkgo biloba and their regulatory role in terpene trilactones biosynthesis - Ang Xu; Chenglin Luo; Chunxia Chen; Yumeng Gao; Wenjing Qin; Qi Wang; Lisha Shi; Xiaoming Yang; Meiling Ming; Fuliang Cao; Fangfang Fu (Plant Science, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Assessment of Spirulina Residue Meal as a Substitute for Fish Meal in Juvenile Rainbow Trout (Oncorhynchus mykiss) Diets: Impact on Growth, Antioxidative Capacity, Carcass Composition and Hepatointestinal Health - Ning Fu; Yuyu Wang; Shengwen Niu; Mengxin Xing; Meiling An; Lu Zhao; Gefeng Xu; Hairui Yu; Jiubo Cui (Fishes, 2026)
A 7-week study was conducted to investigate the effects of replacing fish meal (FM) with Spirulina residue meal (SPRM) on the growth, feed utilization, carcass composition, antioxidant ability, liver and intestinal histology of juvenile rainbow trout (Oncorhynchus mykiss) (initial body weight 5.36 ± 0.04 g). Four isonitrogenous (42%) and isolipidic (16%) diets were formulated to replace FM protein with SPRM at 0 (SPRM0), 10% (SPRM10), 20% (SPRM20) and 30% (SPRM30), respectively. Results showed that growth, feed utilization, carcass amino acid profile, serum biochemical indices, antioxidant ability, intestinal and liver histology were not significantly affected by dietary SPRM levels. Whole-body lipid content decreased as dietary SPRM replacement levels increased, and fish fed diet SPRM30 had lower lipid content than that fish fed diet SPRM0 (p 0.05). The muscle C22:6n-3 (DHA) content decreased, but C18:3n-6 and n-6/n-3 polyunsaturated fatty acid (PUFA) ratio increased with increasing SPRM levels, and fish fed diet SPRM30 had significantly lower DHA content and higher n-6/n-3 ratio than the group fed SPRM0 (p 0.05), but higher than the SPRM10 and SPRM20 groups (p

Global distribution of the terrestrial moisture dynamics response to the meteorological dry-wet abrupt alternation - Jianyu Fu; Mingzhu Cao; Yang Lu; Chunzhu Wei; Xuejin Tan; Meiling Zheng; Liqian Peng; Wenhao Jia; Bingjun Liu (Journal of Hydrology, 2026)

Exogenous plant growth-promoting rhizobacteria boosting photosynthetic efficiency via thylakoid lipid restructuring in potato under low-potassium conditions - Xin Zhou; Xin Cheng; Baoyu Fu; Meiling Li; Chao Luo; Haoyang Gong; Hongkun Yang; Jingye Fu; Chengcheng Cai; Kaiqin Zhang; Shunlin Zheng (Plant Science, 2026)

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

SREBP1-activated lipid metabolism drives ferroptosis and progression of clear cell renal cell carcinoma - Bao Wang; Junpeng Fu; Jian Qian; Yuang Wei; Meiling Bao; Haoqi Miao; Xinzhe Zhao; Kezheng Shao; Yuan Song; Ruoyun Tan; Jie Li; Pengfei Shao (Science China Life Sciences, 2026)

Impact of Drought‐Flood Abrupt Alternation on Vegetation Productivity in Karst and Non‐Karst Regions of Southern China - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (International Journal of Climatology, 2026)
Drought‐flood abrupt alternation (DFAA)—characterised by rapid transitions between drought and flood events—is an extreme compound natural hazard that threatens ecosystems, particularly in fragile environments such as karst regions. Soil moisture is a key indicator of surface hydrological processes, directly regulating vegetation growth and recovery. This study utilises the Standardised Soil Moisture Index (SSMI) to identify DFAA events and applies Granger causality analysis to reveal soil moisture‐vegetation interactions. The impact of DFAA on vegetation productivity is quantified, with a comparative analysis between karst and non‐karst regions in southern China. The results indicate that: (1) From 2000 to 2020, SSMI showed a significant upward trend. Drought‐to‐flood events were more frequent, intense, and longer in duration than flood‐to‐drought events. Both types of events also exhibited substantial spatial heterogeneity. (2) SSMI and NDVI were positively correlated, with the strongest correlation reaching 0.32 at a 60‐day lag. Bidirectional causality between SSMI and NDVI was predominant, affecting 49.24% of the study area. (3) Flood‐to‐drought events synergistically intensified drought–flood stress, whilst drought‐to‐flood events mitigated stress effects. Consequently, vegetation recovery was slower after flood‐to‐drought events, particularly in hydrologically vulnerable karst regions.

The BBX Gene Family in Papaya (Carica papaya L.): Genome-Wide Identification and Expression Profiling During Fruit Ripening - Meiling Ding; Shengjie Li; Jialin Hu; Sicheng Bai; Xianqi Fu; Zhimiao Liang; Xiaomin Liang; Yating Li; Miaoyu Zhao (Tropical Plant Biology, 2025)

EDIL3 induced by GLIS2 suppresses the anti-tumor activity of CD8+ T cells and expedites epithelial-mesenchymal transition in thyroid cancer - Xu Qian; Bo Fu; Shuangfu Peng; Meiling Xue; Zhaohui Zhu; Dan Yao (Journal of Molecular Histology, 2025)

Impact of soil moisture depth variation on agricultural drought monitoring in karst and non-karst areas of southwest China: a case study of Yunnan Province - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (CATENA, 2025)

Hierarchically superhydrophobic ceramic fiber membrane with thermal-induced pore modulation for antifouling oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Huaiyuan Wang (Chemical Engineering Journal, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

CO2 selective adsorption from CO2/CH4 mixtures and regeneration of X zeolites by Li and K modification using various regeneration strategies - Yongbiao Sun; Hui Li; Haijun Lai; Yan Yu; Meiling Hou; Chao Fu; Zaizhou Wang; Chunxiang Zhang (Chemical Engineering Journal, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Divergent trends in vegetation greenness and resilience across China's forestry ecological engineering regions - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Ecological Engineering, 2025)

Construction of site-specific immobilized lipase in bio-inspired “rigid and flexible” composite PVIm/ZIF-8 for long-cycle biodiesel synthesis from waste cooking oil - Qian Wang; Xinyuan Zheng; Meiling Ge; Rong Chen; Fangpei Ma; Jianming Pan; Fu Yang (Chemical Engineering Journal, 2025)

Ecosystem resilience response to forest fragmentation in China: Thresholds identification - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Journal of Environmental Management, 2025)

Spatiotemporal changes of vegetation in the northern foothills of Qinling Mountains based on kNDVI considering climate time-lag effects and human activities - Lili Chen; Zhenhong Li; Chenglong Zhang; Xinxin Fu; Jiahao Ma; Meiling Zhou; Jianbing Peng (Environmental Research, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Interfacial charge demulsification endowed dual-network photocatalytic hydrogen-bonded PVA@agarose membranes for oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Liyan Liu; Huaiyuan Wang (Journal of Hazardous Materials, 2024)

Coupled physicochemical dual-crosslinking Ti3C2T composite aerogels for the selective adsorption of gallium ions in acid fly ash leaching - Xiaopei Zhang; Weifeng Liu; Chang Liang; Dongju Fu; Meiling Wang; Xuguang Liu (Journal of Hazardous Materials, 2024)

MXene-based composite aerogels with bifunctional ferrous ions for the efficient degradation of phenol from wastewater - Gaoyuan Li; Weifeng Liu; Shaojun Gao; Huayu Lu; Dongju Fu; Meiling Wang; Xuguang Liu (Chemosphere, 2024)

Novel superhydrophobic sponge with flower-like architecture for oily emulsion separation and organic pollutants photodegradation - Jinyue Yang; Zhanjian Liu; Jing Jing; Xiguang Zhang; Yuxin Fu; Meiling Li; Huaiyuan Wang (Journal of Environmental Chemical Engineering, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Topological analysis, endogenous mechanisms, and supply risk propagation in the polycrystalline silicon trade dependency network - Chaohao miao; Yanfang wan; Meiling kang; Fu Xiang (Journal of Cleaner Production, 2024)

Thermo-responsive ion imprinted polymer on the surface of magnetic carbon nanospheres for recognizing and capturing low-concentration lithium ion - Chang Liang; Xiaopei Zhang; Weifeng Liu; Xingfu Song; Shuying Sun; Dongju Fu; Geng Dong; Meiling Wang; Yonghui Bai; Xuguang Liu (Minerals Engineering, 2023)

Analysis of seismic escape accessibility and risk in old community with unreinforced masonry buildings - Meiling Xiao; Jianbin Xie; Cuilin Liu; Haiyan Zhu; Yong Zhu; Yujie Fu; Jun Ren (Stochastic Environmental Research and Risk Assessment, 2023)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

Eco-friendly waterborne superhydrophobic/superoleophilic FEVE composite coating with prolonged mechanochemical and anti-scaling properties - Zhanjian Liu; Lina Ren; Baoshuang Zhang; Jing Jing; Xiguang Zhang; Meiling Li; Yuxin Fu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

MicroRNA-375 overexpression disrupts cardiac development of Zebrafish (Danio rerio) by targeting notch2 - Sisi Zhuang; Yanrong Fu; Jingyun Li; Mengmeng Li; Xiaoshan Hu; Jingai Zhu; Meiling Tong (Protoplasma, 2020)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Periodic Variation of AAK1 in an Aβ1–42-Induced Mouse Model of Alzheimer’s Disease - Xue Fu; Meiling Ke; Weihua Yu; Xia Wang; Qian Xiao; Min Gu; Yang Lü (Journal of Molecular Neuroscience, 2018)